Ambipolar ferromagnetism by electrostatic doping of a manganite - L. M. Zheng (Nature Portfolio, 2018)
An ambipolar ferromagnet with both electron- and hole-doped ferromagnetism in a single material would facilitate understanding of ferromagnetic semiconductors for spintronic applications. Here the authors demonstrate ambipolar ferromagnetism in LaMnO3, using ionic liquid gating enabled electrostatic doping to produce electron–hole asymmetry.